Case Report: Hematoma Formation After Spontaneous Coronary Artery Rupture - Liang, Weitao; Yue, Honghua; Zhang, Tailong; Wu, Zhong (Frontiers in Cardiovascular Medicine, 2022)
We report a case of hematoma formation in the right coronary artery after spontaneous rupture. A 48-year-old female patient was admitted with a suspected right cardiac mass. Despite diagnostic work-up, the dignity of the mass could not be determined. Due to acute clinical symptoms, explorative surgery was decided and performed. Hereby, the mass was partially incised, and thrombus-like tissue was detected without active bleeding. We described the challenges during the diagnostic process, and the diagnosis was finally made according to a multimodality approach. For further assessment, we reviewed related literature and highlighted the importance of coronary angiography in the preoperative evaluation of such patients. The therapy may vary according to the location and size of such lesions.